Networking Governance in Waste Management in Pekanbaru City - Hasim As’ari; Nurlaila Meilani; Ahmad Hadi; M. Arphin Dita; Nur Maharani Zurima; Anggi Hawarnia Batubara; Mawaddah Waramah (LITERACY : International Scientific Journals of Social, Education, Humanities, 2026)
The issue of waste in urban areas, particularly in rapidly growing cities like Pekanbaru, has become a significant challenge for sustainable development. Waste composition is dominated by household waste, food scraps, plastics, paper, and waste from the trade and service sectors. This study aims to explore waste management in Pekanbaru City through the lens of networking governance, focusing on collaboration among various stakeholders. The research questions address who the key actors in waste management are, their roles, relationships, and the dynamics of networking governance. Additionally, it investigates the obstacles faced by the system and efforts to overcome these challenges. According to the 2024 DLHK report, the city's waste collection capacity is only able to handle 70% of daily waste, with the remaining waste accumulating in temporary storage areas, drainage systems, and vacant lots, creating environmental and public health risks. By mid-2025, Pekanbaru's waste management will rely heavily on third-party contractors. Using qualitative methods and a phenomenological approach based on Klijn and Koppenjan’s (2016) Network Governance theory, this research will examine networking management, actors, interdependencies, institutional features, and the interactions involved. The findings are expected to provide data-driven policy recommendations for improving waste management in a sustainable, equitable manner. The research will also contribute scientific outputs in the form of indexed articles, comprehensive monographs, policy briefs, and documentary videos documenting the research activities.